Penguatan Ideologi Aisyiyah dan Profesionalisme Pendidik TK/KB ABA dalam Mewujudkan Pendidikan Berkemajuan - Husnatul Mahmudah; Zuhrah; Juhriati; Rahmawati; Retnoningsih; Nurfarhaty (Sarau Institute, 2026)
Aisyiyah Bustanul Athfal Kindergartens and Playgroups (TK/KB ABA) have been integral to the Aisyiyah movement’s early childhood education mission since 1919. Strengthening organizational ideology is essential for enhancing teachers’ professionalism and fostering children’s character development. This community service program addressed the varying levels of teachers’ understanding of Al-Islam and Muhammadiyah (AIK) values, Aisyiyah ideology, and their integration into twenty-first-century learning. The program aimed to strengthen ideological understanding and professional competence through a Participatory Action Research (PAR) approach involving needs assessment, Baitul Arqam training, workshops on progressive Islamic learning design, mentoring, and continuous evaluation. The program involved 48 TK/KB ABA teachers affiliated with the Aisyiyah Bustanul Athfal Teachers Association (IGABA) in Bima Regency, West Nusa Tenggara. Results showed a 41% increase in ideological understanding and a 37% improvement in professional competence, alongside enhanced ability to integrate tauhid, moral values, and modern science into contextual learning through a sustainable mentoring model.